IMPLEMENTASI KEBIJAKAN RENCANA KERJA PEMERINTAH DESA (RKPDES) DALAM PEMBANGUNAN DI DESA KOTABARU SEBERIDA KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2019-2020 - Wahyuni Putri Pratama; Auradian Marta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT The government realizes the importance of rural development. In looking at efforts to increase village development through the Village Government Work Plan (RKPdes), a reference is needed to look at the Village Medium-Term Development Plan (RPJMdes). village development can run well.. The aim of the research is to find out the implementation of the Village Government Work Plan (RKPDes) policy in development in Kotabaru Seberida Village, Keritang District, Indragiri Hilir Regency in 2019-2020. This study uses a qualitative approach which examines all available data from various sources, namely interviews, observations that have been written down in notes, fields, personal documents, official documents, pictures, photographs. The results of this study are that the Implementation of the Village Government Work Plan (RKPDes) Policy in Development in Kotabaru Seberida Village in 2019-2020 has not been optimal in terms of communication indicators between the village head and village government officials, village head with the community and village head with the district government. resources in the form of human resources, budgetary resources and supporting resources. implementing attitude and bureaucratic structure in the form of village government and community participation in carrying out the RKPDes policy. Keywords : Communication, Resources, Dispositions Or Attitudes, Bureaucratic Structure